The importance of quality accounting information management in regional governments in Indonesia - Hari Setiyawati; Caturida Meiwanto Doktoralina (Management Science Letters, 2019)
This study aims to determine the influence of information technology utilisation and the application of good governance principles on the quality of accounting information. The survey is an explanatory research intending to explain the causal relationships between variables through testing hypothe-ses. The analysis is used to determine the independent variables’ influence on the dependent variable. This research is conducted based on existing theories which were later developed into a research model designed to examine the effect of information technology utilisation and the application of good governance principles on the quality of accounting information. The study aims to re-view the quality of accounting information to answer research questions concerning the effect of in-formation technology utilisation and the application of principles of good governance on the quality of accounting information. The benefit of this research is that it contributes scientifically to financial accounting and public sector science and it attempts to solve the problems stakeholders face when implementing tasks related to the quality of accounting information. The study results state that the use of information technology affects the quality of accounting information, as does the application of good governance principles. This study’s implications will help raise awareness concerning the importance of integrity in the accounting reporting system in regional governments in Indonesia.